PASEMAYAN PAWIWAHAN DALAM PERKAWINAN HUKUM ADAT BALI - Dewa Krisna Prasada (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Marriage in Balinese customary law is known as pawiwahan or wiwaha. Marriage in national law is regulated in Law Number 1 of 1974. The biggest problem in marriage is divorce which ends in conflict over property, both congenital and collective assets. Preventive action to prevent the above problems is by making a marriage agreement. This research focuses on normative legal research type that puts emphasis on the vagueness of norms in the marriage law regarding marriage agreements and explores more clearly the form and content of the marriage agreement in Balinese customary law. The result of this research is a form of marriage agreement, which is a written agreement made and legalized by a notary before the marriage is conducted. The contents of the marriage agreement include the classification of inherited and joint assets of the parties. In the making of this marriage agreement, good consequences are considered legally, psychologically, sociologically and culturally by the existence of this marriage agreement legal action. Perkawinan dalam hukum adat Bali dikenal dengan istilah pawiwahan atau wiwaha. Perkawinan dalam hukum nasioan diatur dalam Undang-Undang Nomor 1 Tahun 1974. Permasalahan terbersar dalam perkawinan yaitu perceraian yang berujung dengan konflik perebutan harta benda baik itu bawaan ataupun harta bersama. Tindakan preventif untuk mencegah terjadinya permasalahan diatas yaitu dengan dibuatnya perjanjian perkawinan. Penelitian ini akan berfokus pada jenis penelitian hukum normatif (normative legal research) yang menitik beratkan adanya kekaburan norma dalam undang-undang perkawinan mengenai perjanjian perkawinan serta mengulik lebih jelas bagaimana bentuk dan isi perjanjian perkawinan dalam hukum adat Bali. hasil dari riset ini yaitu bentuk perjanjian perkawinan yaitu perjanjian tertulis yang dibuat dan disahkan oleh notaris yang dibuat sebelum melangsungkan perkawinan. Isi dari perjanjian perkawinan antara lain pengkalsifikasian harta benda bawaan dan harta bersama para pihak. dalam pembuatannya perjanjian perkawinan ini tentunya ada akibat-akibat baik secara hukum, psikologis, sosiologis dan budaya dengan adanya perbuatan hukum perjanjian perkawinan ini